Occurrence Of CTX-M I gene in Beta lactam resistance Neisseria gonorrhoeae isolated Form women with endocervical infection - Ahmed Sadoon Hassain; Thanaa Rasheed Abdulrahman; Jabbar S. hassan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Gonococcus is one of the virtually bacteria related to sexually transmitted diseases with high genetic variability, making it more prone to the acquisition of antibacterial resistance particularly to extended-spectrum β-lactamases (ESBLs). In the last years, the most prevalent ESBLs are of the CTX-M type.Aim: To investigate the occurrence of CTX-M I gene in Beta lactam resistance Endocervical infection-related Neisseria gonorrhoeae isolated from female patients.Methods: Fifteen Neisseria gonorrhoeae isolates that previously recovered from endocervical swab samples of women with bacterial vaginosis were used in this study. All bacterial isolates and they're resistant to different antibiotics were investigated by VITEK 2 microbial identification system. After plasmid DNA extraction, monoplex-PCR with primer sequences targeting plasmid - mediated -blaCTX-MI resistance gene was used.Results: Out of Fifteen isolates of resistant Neisseria gonorrhoeae, the plasmid-mediated blaCTXMI resistant gene was detected in 9 (60%) with amplicon product (499 pb).Conclusions: The emergence of the CTX-M I gene in Neisseria gonorrhoeae is a major threat to the current beta lactam antibiotics that are used in the treatment of gonorrhea in our country.